2022
DOI: 10.5812/aapm.123463
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Analgesic Modalities on Postoperative Cancer Recurrence

Abstract: : The potential for cancer cells to grow and to metastasize depends on complex interactions between inflammatory signals and pathways, immune cells, and elements of the stromal tissue in which they invade. Related to the nature of many cancers, the probability of recurrence can potentially be quite high for some patients. Immunology, lifestyle modifications, timing of disease, genetics, age, gender, and race are only a handful of ways the likelihood of cancer recurrence can be influenced. The quantity, or dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…[34–36] Therefore, dexmedetomidine exerts a therapeutic and preventive effect on serotonin syndrome. [12,13] In the present case, the patient had a combination of neuropathic pain, anxiety, and a history of serotonin syndrome. Therefore, the subsequent selection of dexmedetomidine and sufentanil for analgesia is of great significance.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…[34–36] Therefore, dexmedetomidine exerts a therapeutic and preventive effect on serotonin syndrome. [12,13] In the present case, the patient had a combination of neuropathic pain, anxiety, and a history of serotonin syndrome. Therefore, the subsequent selection of dexmedetomidine and sufentanil for analgesia is of great significance.…”
Section: Discussionmentioning
confidence: 79%
“…[12] Preclinical investigations have suggested promising prospects for COX inhibitors in preserving cancer immune function, possibly providing better options for decreasing cancer recurrence and proliferation. [13] Additionally, celecoxib can reverse immune suppression and counteract the proangiogenic effects of opioid medications in mice. [13] Clinical studies have revealed that the combination of diclofenac or celecoxib with opioid drugs can significantly control bone metastasis-associated cancer pain and that celecoxib can alleviate adverse reactions associated with increasing opioid dosage.…”
Section: Analysis Of the Rationality Of The Treatment Plansmentioning
confidence: 99%
See 1 more Smart Citation
“…Sevoflurane has been shown to induce T-lymphocyte apoptosis, reduce natural killer (NK) cell activity, reduce Th1 / Th2 ratio, increase tumorigenic cytokines and matrix metalloproteinases (MMPS) levels (key enzymes involved in basement membrane disassembly, thereby promoting tumor dissemination) to systematically damage immune function [ 14 , 15 ]. In contrast, propofol increased the activity of cytotoxic t-lymphocytes, does not inhibit the activity of the NK cells, and reduced the tumorigenic cytokines, has the protective and anticancer effects [ 16 ]. Propofol can also inhibit matrix metalloproteinases, it has the anti-tumor characteristics [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is concern about the protumor effects that opioids may have [36]. From an oncogenic point of view, opioid receptors have been associated with phenomena such as angiogenesis and neovascularization through various pathways [37].…”
Section: Opioidsmentioning
confidence: 99%